Comparison of different PCR approaches for characterization of Burkholderia (Pseudomonas) cepacia isolates. - Liu, P Y (1995)
In this study, we evaluated three PCR methods for epidemiological typing of Burkholderia (Pseudomonas) cepacia--PCR-ribotyping, arbitrarily primed PCR (AP-PCR) and enterobacterial repetitive intergenic consensus sequence PCR (ERIC-PCR)--and compared them with pulsed-field gel electrophoresis. The analysis was performed with 31 isolates of B. cepacia, comprising 23 epidemiologically unrelated isolates and 8 isolates collected from the same patient during two episodes of bacteremia. Pulsed-field gel electrophoresis, ERIC-PCR, and AP-PCR identified 23 distinct types among the 23 unrelated isolates, while PCR-ribotyping only identified 12 strain types, even after AluI digestion of the amplification products. Among the eight isolates collected from the same patient, all typing techniques revealed two clones of strains. The day-to-day reproducibilities of PCR-ribotyping and ERIC-PCR were good, while greater day-to-day variations were noted in the fingerprints obtained by AP-PCR. We conclude that all three PCR techniques are useful for rapid epidemiological typing of B. cepacia, but ERIC-PCR seems to be more reproducible and discriminative.